Double-alloy sintered neodymium-iron-boron permanent magnet and preparation method and application thereof

By using the dual alloy method in the NdFeB permanent magnet and combined with a specific process flow, the problem of the doping of alloy elements in the prior art affects the magnetic properties, and the effect of improving mechanical properties while ensuring magnetic properties is achieved.

CN119673647APending Publication Date: 2025-03-21MIANYANG JUXING PERMANENT MAGNET MATERIAL CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411807723.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Although the prior art can improve the mechanical properties of neodymium iron boron permanent magnets through alloy element doping, it usually affects the magnetic properties, making it difficult to further improve the mechanical properties while ensuring magnetic properties.

Method used

The dual alloy method is adopted to control the ratio of Al, RE2 and M elements by adding auxiliary alloys with AlRE2M components to the main alloy, and the dual alloy NdFeB permanent magnets are prepared by fast-condensing process, hydrogen crushing, airflow grinding, orientation pressure, cold isostatic pressure, liquid phase sintering and tempering heat treatment.

Benefits of technology

While improving the mechanical properties of neodymium iron boron permanent magnets, the magnetic properties are synchronously optimized to ensure good consistency and stability of mechanical properties and magnetic properties. The process is simple and easy to perform, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119673647A_ABST
    Figure CN119673647A_ABST
Patent Text Reader

Abstract

The invention discloses a double-alloy sintered neodymium-iron-boron permanent magnet and a preparation method and application thereof, and relates to the technical field of rare earth permanent magnet materials. Comprising the following steps that a main alloy and an auxiliary alloy are evenly mixed and then subjected to orientation profiling, cold isostatic pressing, liquid phase sintering and tempering heat treatment in sequence, the double-alloy neodymium iron boron permanent magnet is prepared, the chemical composition of the auxiliary alloy is AlxRE2yM100-x-y, RE2 is selected from one or more combinations of Ce, Dy, Gd, Ho, La, Nd, Pr, Tb and Y, and M is selected from any one or more combinations of Co, Cu, Ga, Ti, Zr and Nb; x and y satisfy 5 < = x < = 50 and 20 < = y < = 80; according to the method, on the premise that the magnetic performance of the neodymium iron boron permanent magnet is synchronously optimized, the mechanical performance of the neodymium iron boron permanent magnet is further improved, the mechanical performance and the magnetic performance of the sintered magnet have good consistency and stability, the technological method is simple and easy to implement, and the method is suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rare earth permanent magnet materials, and in particular to a double alloy sintered NdFeB permanent magnet and a preparation method and application thereof. Background Art

[0002] Sintered NdFeB permanent magnet is an excellent magnetic functional material. Various functional devices made by its magnetic effect are now widely used in electronic communications, medical equipment, aerospace and other fields. Since the advent of NdFeB materials, researchers have greatly improved the magnetic properties of NdFeB magnets by improving processes, component design, boundary strengthening, grain boundary diffusion and other methods. With the development of social productivity, the application field of sintered NdFeB continues to expand. Its exposed problems such as peeling, edge loss, corner loss, and cracking limit its application in vibration environments or under extremely high acceleration conditions. Therefore, improving the mechanical properties of sintered NdFeB magnets while ensuring the stability of their magnetic properties is the goal of common efforts in the field of NdFeB permanent magnets.

[0003] Research shows that under the action of external stress, the grain boundary phases and some grains at different positions of the NdFeB permanent magnet will crack to varying degrees, and these cracks will continue to expand and connect with the stress until the permanent magnet is completely broken. Therefore, jointly strengthening the toughness and coupling degree of the grain boundary phase and the main phase grains is the key to improving the comprehensive mechanical properties of NdFeB permanent magnets.

[0004] In the process of preparing permanent magnets, alloy element doping can effectively enhance the toughness and coupling of each phase, thereby greatly improving the macroscopic mechanical properties of the permanent magnet. Research experience shows that although alloy element doping can improve the macroscopic mechanical properties of the permanent magnet to a certain extent, it usually affects the magnetic properties of the permanent magnet to a certain extent. Therefore, there is an urgent need for a method to improve the mechanical properties of the permanent magnet while ensuring that its magnetic properties are not affected or even improved. Summary of the invention

[0005] The present invention aims to solve the technical problem that the mechanical properties and magnetic properties of permanent magnets cannot be improved by doping with alloy elements in the prior art. The invention aims to provide a double-alloy sintered NdFeB permanent magnet and a preparation method and application thereof, which further enhances and improves the macroscopic mechanical properties of the NdFeB permanent magnet under the premise of synchronous optimization of the magnetic properties of the NdFeB permanent magnet, and satisfies the requirement that the mechanical properties and magnetic properties of the magnet after sintering have good consistency and stability, and the process method is simple and easy to implement, and can be applicable to industrial production.

[0006] The present invention is achieved through the following technical solutions:

[0007] The first object of the present invention is to provide a method for preparing a double alloy sintered NdFeB permanent magnet, comprising the following steps:

[0008] The main alloy and the auxiliary alloy are separately batched and melted, and then rapidly solidified to obtain the main alloy casting sheet and the auxiliary alloy casting sheet, and hydrogen crushing and air flow grinding are carried out in sequence to obtain the main alloy powder and the auxiliary alloy powder, and then the main alloy powder and the auxiliary alloy powder are uniformly mixed, and then oriented pressing, cold isostatic pressing, liquid phase sintering, and tempering heat treatment are carried out in sequence to obtain the dual alloy NdFeB permanent magnet;

[0009] The chemical composition of the auxiliary alloy is Al x RE2 y M 100-x-y , wherein Al is aluminum, RE2 is selected from a combination of one or more of Ce, Dy, Gd, Ho, La, Nd, Pr, Tb, and Y, and M is selected from a combination of one or more of Co, Cu, Ga, Ti, Zr, and Nb; x and y correspond to the mass percentage content of the element, respectively, and satisfy 5≤x≤50, 20≤y≤80.

[0010] Furthermore, the preferred range of x is 10 to 30, more preferably 15 to 25, and most preferably 20; the preferred range of y is 30 to 60, and more preferably 35 to 40. Among them, the content of Al will affect the squareness of the permanent magnet, and excessive addition will lead to a decrease in (BH)max; the content of RE2 will affect the wettability of the auxiliary alloy, and too high or too low will cause some elements to segregate.

[0011] Furthermore, the mass ratio of the auxiliary alloy to the main alloy is (0.1-20):100. Preferably, the mass ratio of the auxiliary alloy to the main alloy is (0.5-5):100.

[0012] Furthermore, the chemical composition of the main alloy is: RE1 a M b Fe 100-a-b-c B c , wherein RE1 is selected from any one or more combinations of Pr, Nd, Ce, La, Gd, and Ho, M is selected from any one or more combinations of Co, Cu, Ga, Ti, Zr, and Nb, Fe is iron, and B is boron; a, b, and c correspond to the mass percentage content of the elements, respectively, and satisfy 20≤a≤40, 0.5≤b≤5, and 0.5≤c≤1.5.

[0013] Preferably, the selection range of a is 25 to 35, more preferably 28 to 30, and most preferably 29.5; the selection range of b is 1 to 3, more preferably 2, and c is preferably 0.8 to 1. If the rare earth content is too low, it will lead to the formation of impurity phases such as αFe, which will affect the decrease of coercive force in the magnetic properties of the permanent magnet; if the boron content is too low, it will lead to the inability to form the main phase of NdFeB, and if it is too high, a non-ferromagnetic phase will be formed in the main phase, resulting in a decrease in the magnetic properties of the permanent magnet; the inventors have shown through long-term research that the comprehensive performance of the permanent magnet can be maintained at a relatively high level within the preferred scheme.

[0014] The uniform mixing process adopts three-dimensional motion mixing, and the mixing time is 2 to 10 hours, preferably 5 to 10 hours. If the mixing time is too short, the powder will be uneven, resulting in serious element segregation.

[0015] The particle size of the main alloy powder and the auxiliary alloy powder is 1 to 4 μm; the thickness of the main alloy casting sheet and the auxiliary alloy casting sheet is preferably 0.1 to 0.4 mm, more preferably 0.2 to 0.4 mm; if the main alloy casting sheet and the auxiliary alloy casting sheet are too thick, the internal grain size will be uneven, and if they are too thin, the casting sheet will be herringbone-shaped and the organizational structure will not be continuous enough. At the same time, the output will be reduced, resulting in waste of raw materials.

[0016] Specifically, the hydrogen crushing process is preferably rotary hydrogen crushing, and the rotation speed is preferably 2-3r / min; the hydrogen filling pressure is preferably 0.1-0.4MPa, more preferably 0.2-0.3MPa; the hydrogen absorption time is preferably 2-10h; the dehydrogenation temperature is 320-750°C; the dehydrogenation is preferably vacuum dehydrogenation; the dehydrogenation time is 4-10h. Rotary hydrogen crushing is conducive to the full hydrogen absorption and crushing of the alloy casting. Too fast a rotation speed will cause the equipment to be overloaded, and too slow a rotation speed will not ensure that the alloy casting fully absorbs hydrogen; too low a hydrogen pressure will make the hydrogen absorption too slow, and too high a hydrogen pressure will cause unnecessary waste and bring risks to the pressure bearing capacity of the equipment; too long a hydrogen absorption time will reduce the process efficiency, and too short a hydrogen absorption time will result in insufficient hydrogen absorption.

[0017] In the present invention, the hydrogen content of the coarsely crushed powder obtained after hydrogen crushing is preferably less than 500 ppm, and the average particle size of the powder is 80 to 200 microns. If the hydrogen content of the coarsely crushed powder is too high, the degassing efficiency during the heating process of the sintering process will be reduced, and too much hydrogen will deteriorate the magnetic properties of the final magnet.

[0018] In the present invention, the moisture content of the mill during the airflow milling process is preferably less than 10 ppm, and the rotation frequency of the classifying wheel is preferably 65 to 110 Hz. Too high moisture content in the airflow mill will cause the permanent magnet to have excessive oxygen content, which will lead to deterioration of magnetic properties.

[0019] Furthermore, the orientation pressing is performed in a magnetic field, and the pressure of the pressing is 40-60MPa, preferably 50MPa. Too little pressure will make the permanent magnet blank too loose, which is not conducive to the subsequent sintering process; too much pressure will cause the density of the permanent magnet blank to be too high and the orientation degree to be too low. The magnetic field strength used in the orientation pressing process is 0.5-3T, preferably 2-3T.

[0020] Furthermore, the pressure used in the cold isostatic pressing process is 100-300 MPa, preferably 200-250 MPa; too low a pressure will make the density of the permanent magnet blank too low, and a hole structure will easily appear; too high a pressure will cause the permanent magnet blank to crack.

[0021] Furthermore, the liquid phase sintering is preferably vacuum liquid phase sintering; the liquid phase sintering heating process is continuous step-wise heating. In the present invention, the heating time is preferably 3 to 20 hours, more preferably 5 to 10 hours, wherein a too short heating time of the liquid phase sintering will lead to incomplete gas release during the liquid phase sintering process, resulting in too low density of the permanent magnet and easy presence of a pore structure, and a too long heating time of the liquid phase sintering will affect the efficiency of permanent magnet preparation.

[0022] Furthermore, the temperature of the liquid phase sintering is 1000-1200°C, and the time of the liquid phase sintering is 2-6 hours, preferably 3-5 hours. If the liquid phase sintering time is too short, it will lead to permanent magnets, and if the liquid phase sintering time is too long, the grains will grow abnormally, resulting in a significant deterioration of the magnetic properties of the permanent magnets.

[0023] Furthermore, the tempering heat treatment includes primary tempering and secondary tempering, the primary tempering is at 700-950°C, the secondary tempering is at 400-600°C, and the time of the primary tempering and the secondary tempering are independently 0.5-3h.

[0024] The second object of the present invention is to provide a NdFeB permanent magnet prepared by the above method.

[0025] The third object of the present invention is to provide an application of an iron boron permanent magnet in electric two-wheeled vehicles, the automotive industry, electronic products, wind power, elevators, industrial robots or humanoid robots.

[0026] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0027] 1. The present invention adds an auxiliary alloy of AlRE2M components to the main alloy, strictly screens the composition of the auxiliary alloy, and controls the ratio between Al, RE2 elements and M within a suitable range, thereby achieving the goal of improving the magnetic properties of the permanent magnet while improving the mechanical properties of the permanent magnet. The obtained dual-alloy NdFeB permanent magnet has good consistency and stability. After multiple experimental demonstrations, the process method is simple and easy to implement, can be applied to industrial production, and has great significance for the practical application of sintered NdFeB.

[0028] 2. The aluminum element in the auxiliary alloy added by the present invention is distributed in the main phase grains and grain boundaries of NdFeB, playing the role of jointly strengthening the grains and grain boundaries, and strengthening the mechanical properties of NdFeB permanent magnets under the condition of improving the magnetic properties to a certain extent. Among them, in the main phase grains, Al atoms preferentially occupy the 8j2 crystal position in the compound, which is located at the center of the hexagonal prism of Fe atoms and has more Fe atoms neighbors. 14 An α-Fe layer is formed in B, which reduces the magnetic moment of Fe atoms near Al atoms, but improves the mechanical properties of the grains to a certain extent; in the grain boundary, Al enters the Nd-rich phase and forms intermetallic compounds with rare earth elements such as Nd, improving the Nd liquid phase and Nd2Fe 14 The wetting angle of the B solid phase makes the Nd-rich phase more evenly distributed along the boundary, resulting in grain refinement and smaller size of the Nd-rich phase and the B-rich phase, which plays a key role in improving the coercive force and mechanical properties of the magnet. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:

[0030] Figure 1 EPMA and Mapping diagram of the double alloy NdFeB permanent magnet of Example 1 of the present invention;

[0031] Figure 2 1 is the bending strength stress-strain curve of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the present invention;

[0032] Figure 3 It is the Vickers hardness indentation SEM picture of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0033] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the technical solutions in the embodiments of the present invention are clearly and completely described below in combination with the embodiments and drawings. Obviously, the schematic implementation modes of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0034] The following is a detailed description of a dual alloy sintered NdFeB permanent magnet and its preparation method and application according to the present invention with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions and repeated descriptions of well-known matters are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art.

[0035] The "range" disclosed in this application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range.

[0036] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0037] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0038] Unless otherwise specified, the terms "include" and "comprising" mentioned in this application may be open-ended or closed-ended. For example, the terms "include" and "comprising" may mean that other substances not listed may also be included or only the listed substances may be included.

[0039] If there is no special explanation, all the steps of the present application can be performed sequentially or randomly, preferably sequentially.

[0040] The technical solution of the present invention is further described in detail below in conjunction with embodiments.

[0041] It should be noted that the experimental methods used in the examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained by those skilled in the art through commercial channels.

[0042] Example 1

[0043] A method for preparing a double alloy sintered NdFeB permanent magnet comprises the following steps:

[0044] (1) Prepare the raw materials according to the main alloy composition and auxiliary alloy composition, where the main alloy composition and mass percentage are Nd 21.73 Pr 6.84 Co 0.52 Cu 0.21 Ga 0.11 Zr 0.31 Fe 69.32 B 0.96 , the auxiliary alloy composition and mass percentage are Al 15.08 Pr 61.86 Nd 19.87 Ga 3.19 The raw materials are melted and poured to obtain the main alloy casting and the auxiliary alloy casting by using the rapid solidification process. The vacuum degree during the rapid solidification process is 3×10 -3 Pa, the copper roller speed is 2.1m / s, the main alloy pouring temperature is 1300℃, the auxiliary alloy pouring temperature is 1150℃, the average thickness of the main alloy casting is 0.25mm, and the average thickness of the auxiliary alloy casting is 0.28mm.

[0045] (2) The main alloy castings and the auxiliary alloy castings obtained in step (1) are placed in a rotary hydrogen crushing furnace in sequence, wherein the furnace tube rotation speed during the hydrogen crushing process is 2 r / min, the hydrogen pressure is 0.4 MPa, the hydrogen absorption time is 4 hours, the dehydrogenation time is 6 hours, the main coarse crushing powder has an average particle size of 166 μm, and the auxiliary coarse crushing powder has an average particle size of 171 μm.

[0046] (3) The primary coarse crushed powder and the auxiliary coarse crushed powder obtained in step (2) are placed in a jet mill in sequence for powder making, wherein the moisture content during the powder making process is 1.5 ppm, the rotation frequency of the grading wheel is 95 Hz, the average particle size of the primary alloy powder is 2.9 μm, and the average particle size of the auxiliary alloy powder is 3.1 μm.

[0047] (4) The main alloy powder and the auxiliary alloy powder obtained in step (3) are weighed in a ratio of 100:3, lubricant is added and mixed evenly, and oriented pressing is performed in an argon atmosphere, wherein the magnetic field strength is 1.6T and the molding pressure is 60MPa. Subsequently, the obtained molded blank is cold isostatically pressed at a pressure of 210MPa to obtain a twice-pressed magnet blank.

[0048] (5) placing the double pressed magnet blank obtained in step (4) in a sintering furnace for vacuum sintering and tempering heat treatment, wherein the sintering temperature is 1055° C., the sintering time is 4.5 hours, the primary tempering temperature is 880° C., the primary tempering time is 1.8 hours, the secondary tempering temperature is 480° C., and the secondary tempering time is 1.8 hours, to obtain a dual alloy NdFeB permanent magnet.

[0049] The EPMA and Mapping images of the double alloy NdFeB permanent magnet prepared in this embodiment are as follows: Figure 1 shown.

[0050] Comparative Example 1

[0051] In the process of preparing the dual alloy NdFeB permanent magnet in this comparative example, the process scheme is different from that in Example 1 in that the Al element is removed from the auxiliary alloy component composition, and the other preparation processes are consistent with those in Example 1.

[0052] Comparative Example 2

[0053] In the process of preparing the dual alloy NdFeB permanent magnet in this comparative example, the process scheme is different from that in Example 1 in that the Pr element is replaced by the Ce element in the auxiliary alloy component, and the other preparation processes are consistent with those in Example 1.

[0054] Comparative Example 3

[0055] In the process of preparing the dual alloy NdFeB permanent magnet in this comparative example, the process scheme is different from that in Example 1 in that the Ga element in the auxiliary alloy component is replaced by the Fe element, and the other preparation processes are consistent with those in Example 1.

[0056] In order to compare the mechanical property strengthening effect of the dual alloy NdFeB permanent magnets prepared in Example 1 and Comparative Examples 1-3, the main alloy powder obtained in step (3) of Example 1 was used to prepare the original permanent magnets by the same vacuum sintering and tempering heat treatment process. Two of the original permanent magnets, the permanent magnets obtained in Example 1 and Comparative Examples 1-3 were randomly selected for magnetic property tests of coercive force and remanence, and mechanical property tests of bending strength and Vickers hardness. The test results are shown in Table 1.

[0057] In addition, the bending strength stress-strain curves of Example 1 and Comparative Examples 1-3 are as follows: Figure 2 As shown, the Vickers hardness indentation SEM images of Example 1 and Comparative Examples 1-3 are as follows Figure 3 shown.

[0058] Table 1, Permanent magnet test data obtained in Example 1 and Comparative Examples 1-3

[0059]

[0060] It can be seen from Table 1 that the permanent magnet prepared by the method of the present invention in Example 1 has improved magnetic properties and mechanical properties compared to the original permanent magnet without adding auxiliary alloy, and has good consistency and stability.

[0061] In Comparative Example 1, the Al element is removed from the auxiliary alloy, and the mass percentages of other elements remain substantially unchanged. From the results, the remanence, coercive force, bending resistance and Vickers hardness of the magnet in Comparative Example 1 are all lower than those of the permanent magnet of the present invention in Example 1.

[0062] In Comparative Example 2, the Pr element in the auxiliary alloy is replaced by the Ce element, and the mass percentages of other elements remain basically unchanged. From the results, the remanence, coercive force, bending resistance and Vickers hardness of the magnet in Comparative Example 2 are all lower than those of the permanent magnet of the present invention in Example 1.

[0063] This is because: in terms of magnetic properties, after Ce enters the main phase, its anisotropy field is much lower than that of rare earth elements such as Pr and Nd, and the atomic magnetic moment of Ce (2.2μB) is much lower than that of rare earth elements such as Pr and Nd. Replacing these rare earth elements with Ce will reduce the overall magnetic moment of the magnet, thereby reducing the remanence. Secondly, Ce may form non-magnetic or weakly magnetic compounds (such as CeFe2 phase) with Fe or other elements. These compounds are distributed at the grain boundaries, which may weaken the pinning effect of the grain boundaries on the main phase, and the Ce-rich grain boundary phase will cause the magnetic mismatch of the main phase grain boundary, promote the reversal of the magnetic domain, and thus reduce the coercive force; in terms of mechanical properties, since the hardness of Ce is much lower than the hardness of the general rare earth-rich phase of NdFeB (Pr, Nd), and the atomic radius of Ce is large, it is easy to cause lattice distortion when entering the NdFeB lattice, thereby affecting the mechanical properties of the material.

[0064] In Comparative Example 3, the Ga element in the auxiliary alloy is replaced by the Fe element, and the mass percentages of other elements remain basically unchanged. From the results, the bending resistance and Vickers hardness of Comparative Example 3 are not much different from those of the permanent magnet of the present invention in Example 1, but the remanence and coercive force of the magnet are lower than those of the permanent magnet of the present invention in Example 1.

[0065] This is because: in terms of magnetic properties, Fe entering the main phase will compete with the main phase for rare earth elements, resulting in a decrease in the rare earth content in the main phase or an increase in the grain size, thereby reducing the remanence and coercivity of the magnet, and Fe combined with rare earths sometimes exists in the form of a soft magnetic iron phase, which will have a diamagnetic effect on the main phase, thereby reducing the remanence and coercivity. In terms of mechanical properties, Fe has high hardness and strength. The addition of Fe-containing auxiliary phases can improve the mechanical properties of the overall material. In addition, the Fe-containing auxiliary phase will form an alloy phase with rare earth elements, which can play a certain strengthening role at the grain boundary, increase the bonding strength of the grain boundary, and thus improve the mechanical properties.

[0066] Based on the test results of Example 1 and Comparative Examples 1-3, it can be seen that only the dual-alloy NdFeB permanent magnet prepared by using the specific auxiliary alloy components of the present invention can improve its macroscopic mechanical properties while maintaining a high performance level of the magnet performance.

[0067] Example 2

[0068] A method for preparing a double alloy sintered NdFeB permanent magnet comprises the following steps:

[0069] (1) Prepare the raw materials according to the main alloy composition and auxiliary alloy composition, where the main alloy composition and mass percentage are Nd 17.21 Ce11.49 Co 0.88 Cu 0.46 Ga 0.18 Ti 0.51 Zr 0.74 Fe 67.55 B 0.98 , the auxiliary alloy composition and mass percentage are Al 21.09 Pr 55.42 Tb 8.74 Dy 11.59 Ga 1.19 Nb 1.97 The raw materials are melted and poured into the main alloy castings and auxiliary alloy castings by using the rapid solidification process. The vacuum degree during the rapid solidification process is 4.02×10 -3 Pa, the copper roller speed is 2.0m / s, the main alloy pouring temperature is 1260℃, the auxiliary alloy pouring temperature is 1110℃, the average thickness of the main alloy casting is 0.22mm, and the average thickness of the auxiliary alloy casting is 0.24mm.

[0070] (2) The main alloy castings and the auxiliary alloy castings obtained in step (1) are placed in a rotary hydrogen crushing furnace in sequence, wherein the furnace tube rotation speed during the hydrogen crushing process is 2.2 r / min, the hydrogen pressure is 0.3 MPa, the hydrogen absorption time is 3 hours, the dehydrogenation time is 8 hours, the main coarse crushing powder has an average particle size of 141 μm, and the auxiliary coarse crushing powder has an average particle size of 127 μm.

[0071] (3) The primary coarse crushed powder and the auxiliary coarse crushed powder obtained in step (2) are placed in a jet mill in turn for powder making, wherein the moisture content during the powder making process is 0.8 ppm, the rotation frequency of the classifying wheel is 90 Hz, the average particle size of the primary alloy powder is 2.5 μm, and the average particle size of the auxiliary alloy powder is 2.2 μm.

[0072] (4) The main alloy powder and the auxiliary alloy powder obtained in step (3) are weighed in a ratio of 100:3, lubricant is added and mixed evenly, and oriented pressing is performed in an argon atmosphere, wherein the magnetic field strength is 1.8T and the molding pressure is 58MPa. Subsequently, the obtained molded blank is cold isostatically pressed at a pressure of 215MPa to obtain a twice-pressed magnet blank.

[0073] (5) placing the double pressed magnet blank obtained in step (4) in a sintering furnace for vacuum sintering and tempering heat treatment, wherein the sintering temperature is 1025° C., the sintering time is 3.8 hours, the primary tempering temperature is 900° C., the primary tempering time is 2 hours, the secondary tempering temperature is 480° C., and the secondary tempering time is 2 hours, to obtain a dual alloy NdFeB permanent magnet.

[0074] Comparative Example 4

[0075] In the process of preparing the dual alloy NdFeB permanent magnet in this comparative example, the process scheme is different from that in Example 2 in that the main alloy powder and the auxiliary alloy powder are weighed in a ratio of 100:10 and then mixed. The other preparation processes are the same as those in Example 2.

[0076] In order to compare the mechanical property strengthening effect of the dual alloy NdFeB permanent magnets prepared in Example 2 and Comparative Example 4, the main alloy powder obtained in step (3) of Example 2 was used to prepare the original permanent magnets by the same vacuum sintering and tempering heat treatment process. Two of each of the original permanent magnets, Example 2 and Comparative Example 4 were randomly selected for magnetic property tests of coercive force and remanence, and mechanical property tests of bending strength and Vickers hardness. The test results are shown in Table 2.

[0077] Table 2, Permanent magnet test data obtained in Example 2 and Comparative Example 4

[0078]

[0079] It can be seen from Table 2 that the permanent magnet prepared by the method of the present invention in Example 2 has improved magnetic properties and mechanical properties compared to the original permanent magnet without adding auxiliary alloy, and has good consistency and stability.

[0080] In comparative example 4, after the amount of auxiliary alloy added was increased, the magnetic properties and mechanical properties were significantly reduced compared with those of example 2.

[0081] A comprehensive comparison of Example 2 and Comparative Example 4 shows that only within the range of the main alloy and the auxiliary alloy set by the present invention can the macroscopic mechanical properties of the magnet be effectively improved without affecting the magnetic properties, while also improving the magnetic properties.

[0082] Example 3

[0083] A method for preparing a double alloy sintered NdFeB permanent magnet comprises the following steps:

[0084] (1) Prepare the raw materials according to the main alloy composition and auxiliary alloy composition, where the main alloy composition and mass percentage are La 3.75 Ce 16.43 G 8.87 Co 0.93 Ga 1.22 Ti 0.13 Zr 0.44 Fe 67.20 B 1.03 , the auxiliary alloy composition and mass percentage are Al 35.31 Pr 37.43 G 3.42 Tb 7.32 Y 11.36 Co 1.62 Cu 1.78Ga 1.13 Nb 0.63 The raw materials are melted and poured to obtain the main alloy casting and the auxiliary alloy casting by using the rapid solidification process. The vacuum degree during the rapid solidification process is 2.8×10 -3 Pa, the copper roller speed is 1.9m / s, the main alloy pouring temperature is 1140℃, the auxiliary alloy pouring temperature is 1090℃, the average thickness of the main alloy casting is 0.35mm, and the average thickness of the auxiliary alloy casting is 0.33mm.

[0085] (2) The main alloy castings and the auxiliary alloy castings obtained in step (1) are placed in a rotary hydrogen crushing furnace in sequence, wherein the furnace tube rotation speed during the hydrogen crushing process is 2 r / min, the hydrogen pressure is 0.38 MPa, the hydrogen absorption time is 4 hours, the dehydrogenation time is 6 hours, the main coarse crushing powder has an average particle size of 118 μm, and the auxiliary coarse crushing powder has an average particle size of 122 μm.

[0086] (3) The main coarse crushed powder and the auxiliary coarse crushed powder obtained in step (2) are placed in a jet mill in turn for powder making, wherein the moisture content during the powder making process is 5.5 ppm, the rotation frequency of the classifying wheel is 85 Hz, the average particle size of the main alloy powder is 2.8 microns, and the average particle size of the auxiliary alloy powder is 3.1 microns.

[0087] (4) The main alloy powder and the auxiliary alloy powder obtained in step (3) are weighed respectively, lubricant is added and mixed evenly, and oriented pressing is performed in an argon atmosphere, wherein the magnetic field strength is 1.7T and the molding pressure is 55MPa. Subsequently, the obtained molded blank is cold isostatically pressed at a pressure of 240MPa to obtain a twice-pressed magnet blank.

[0088] (5) placing the double pressed magnet blank obtained in step (4) in a sintering furnace for vacuum sintering and tempering heat treatment, wherein the sintering temperature is 1010° C., the sintering time is 4.5 hours, the primary tempering temperature is 845° C., the primary tempering time is 2.5 hours, the secondary tempering temperature is 445° C., and the secondary tempering time is 2.5 hours, to obtain a dual alloy NdFeB permanent magnet.

[0089] Comparative Example 5

[0090] In the process of preparing dual alloy NdFeB permanent magnets in this comparative example, the process scheme is different from that in Example 3 in that the main alloy castings and auxiliary alloy castings obtained in the process are placed in a common hydrogen crushing furnace in turn for hydrogen crushing, and the other preparation processes are consistent with Example 3.

[0091] In order to compare the mechanical property strengthening effect of the dual alloy NdFeB permanent magnets prepared in Example 3 and Comparative Example 5, the main alloy powder obtained in step (3) of Example 3 was used to prepare the original permanent magnets by the same vacuum sintering and tempering heat treatment process. Two of the original permanent magnets, the permanent magnets obtained in Example 3 and Comparative Example 5 were randomly selected for magnetic property tests of coercive force and remanence, and mechanical property tests of bending strength and Vickers hardness. The test results are shown in Table 3.

[0092] Table 3, Permanent magnet test data obtained in Example 3 and Comparative Example 5

[0093]

[0094]

[0095] It can be seen from the data in Table 3 that the permanent magnet prepared by the method of the present invention in Example 3 has improved magnetic properties and mechanical properties compared to the original permanent magnet without adding auxiliary alloy, and has good consistency and stability.

[0096] In comparative example 5, a common hydrogen crushing furnace was used for hydrogen crushing treatment, and the magnetic properties and mechanical properties were reduced to a certain extent compared with those in example 2.

[0097] A comprehensive comparison of Example 3 and Comparative Example 5 shows that the rotary hydrogen crushing process adopted in the present invention can enable the alloy flakes to fully absorb hydrogen and crush, which not only improves the powder making efficiency, but also helps to improve the magnetic properties and mechanical properties of the magnet.

[0098] Finally, it should be noted that the above specific embodiments are only used to explain in detail the purpose, technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific implementation method of the present invention and is not used to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above specific embodiments, ordinary technicians in this field should understand that it is still possible to modify the technical solutions recorded in the above embodiments, or to replace or improve some or all of the technical features therein. These modifications, equivalent replacements and improvements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and description of the present invention.

Claims

1. A method for preparing a double alloy sintered NdFeB permanent magnet, characterized in that: The following steps are involved: The main alloy and the auxiliary alloy are separately batched and melted, and then rapidly solidified to obtain the main alloy casting sheet and the auxiliary alloy casting sheet, and hydrogen crushing and air flow grinding are carried out in sequence to obtain the main alloy powder and the auxiliary alloy powder, and then the main alloy powder and the auxiliary alloy powder are uniformly mixed, and then oriented pressing, cold isostatic pressing, liquid phase sintering, and tempering heat treatment are carried out in sequence to obtain the dual alloy NdFeB permanent magnet; The chemical composition of the auxiliary alloy is Al x RE2 y M 100-x-y , wherein Al is aluminum, RE2 is selected from a combination of one or more of Ce, Dy, Gd, Ho, La, Nd, Pr, Tb, and Y, and M is selected from a combination of one or more of Co, Cu, Ga, Ti, Zr, and Nb; x and y correspond to the mass percentage content of the element, respectively, and satisfy 5≤x≤50, 20≤y≤80.

2. The method for preparing a double alloy sintered NdFeB permanent magnet according to claim 1, characterized in that: The x selection range is 10 to 30, and the y selection range is 30 to 60.

3. The method for preparing a double alloy sintered NdFeB permanent magnet according to claim 2, characterized in that: The selection range for x is 15 to 25, and the selection range for y is 35 to 40.

4. The method for preparing a double alloy sintered NdFeB permanent magnet according to claim 1, characterized in that: The mass ratio of the auxiliary alloy to the main alloy is (0.1-20):

100.

5. The method for preparing a double alloy sintered NdFeB permanent magnet according to claim 4, characterized in that: The mass ratio of the auxiliary alloy to the main alloy is (0.5-5):

100.

6. The method for preparing a double alloy sintered NdFeB permanent magnet according to claim 1, characterized in that: The chemical composition of the main alloy is: RE1 a M b Fe 100-a-b-c B c , wherein RE1 is selected from any one or more combinations of Pr, Nd, Ce, La, Gd, and Ho, M is selected from any one or more combinations of Co, Cu, Ga, Ti, Zr, and Nb, Fe is iron, and B is boron; a, b, and c correspond to the mass percentage content of the elements, respectively, and satisfy 20≤a≤40, 0.5≤b≤5, and 0.5≤c≤1.

5.

7. The method for preparing a double alloy sintered NdFeB permanent magnet according to claim 6, characterized in that: The selection range of a is 25-35, the selection range of b is 1-3, and the selection range of c is 0.8-1.

8. The method for preparing a double alloy sintered NdFeB permanent magnet according to any one of claims 1 to 7, characterized in that: The orientation pressing is carried out in a magnetic field, and the molding pressure is 40-60MPa; the pressure used in the cold isostatic pressing process is 100-300MPa; the temperature of the liquid phase sintering is 1000-1200°C, and the time is 2-6h; the tempering heat treatment includes primary tempering and secondary tempering, the primary tempering is 700-950°C, the secondary tempering temperature is 400-600°C, and the time of the primary tempering and the secondary tempering is independently 0.5-3h.

9. A NdFeB permanent magnet prepared by the method according to any one of claims 1 to 8.

10. Use of the NdFeB permanent magnet obtained by the preparation method according to any one of claims 1 to 8 or the NdFeB permanent magnet according to claim 9 in electric two-wheeled vehicles, automobile industry, electronic products, wind power, elevators, industrial robots or humanoid robots.

Citation Information

Cited By

  • A low heavy rare earth automobile driving motor special 40SH neodymium-iron-boron permanent magnet material and a preparation method thereof

    CN122619559A